Advancements in Soil and Sustainable Agriculture - Lavini, Antonella; Sellami, Mohamed Houssemeddine (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
In the face of mounting challenges such as food insecurity and environmental degradation, the significance of sustainable agriculture has become increasingly apparent as a beacon for our collective future. Central to this transformative movement is the profound importance of soil health, which serves as the bedrock for both crop productivity and ecological resilience. The Special Issue "Advancements in Soil and Sustainable Agriculture" boldly ventures into this pivotal realm, unveiling a rich tapestry of groundbreaking research dedicated to preserving soil health and cultivating a more environmentally conscious agricultural landscape. Within the pages of this reprint, a wealth of experimental studies and insightful reviews converge to address a broad spectrum of soil sustainability issues. From innovative nutrient management strategies to the remediation of contaminated soils, the contributors to this Special Issue illuminate the nuanced interplay between agricultural practices and the intricate web of soil health. This comprehensive collection stands as a guiding compass for researchers, shedding light on the complexities of sustainable agriculture and paving the way for a future that harmonizes food security with environmental stewardship. The invaluable insights encapsulated within these pages are poised to propel the frontiers of sustainable agriculture, ensuring a trajectory where the principles of environmental consciousness and resilient food production intertwine seamlessly for generations to come.